Improving cognition in people with multiple sclerosis: study protocol for a multiarm, randomised, blinded trial of multidomain cognitive rehabilitation using a video-serious game (E-SEP cognition) - Arnaud Kwiatkowski; Laurène Norberciak; Bruno Lenne; Béatrice Degraeve; Jessy Davroux; Cécile Donze (BMJ Neurology Open)
Introduction Multiple sclerosis (MS) is a prevalent neurological disease characterised by disseminated areas of demyelination and atrophy within the central nervous system, inducing cognitive disorders in 45%–65% of persons with MS (PwMS). Neuropsychology and neuroimaging studies provide evidence of the effectiveness of cognitive rehabilitation interventions, including memory and attention. Recently, serious game therapy (SGT) has been used in rehabilitation to improve cognitive processing speed. The aim of this study is to describe the protocol of a randomised controlled trial (RCT) to test the efficacy of a tablet-based cognitive home intervention among ambulatory PwMS, in comparison to a standardised neuropsychological rehabilitation.Methods and analysis This will be a parallel-assignment, double-blinded, RCT. One hundred and fifty (75 per arm) PwMS will be randomly assigned to receive cognitive rehabilitation session over 4 months (four 20-min sessions/week) of either: (1) tablet-based SGT or (2) conventional cognitive exercises. The same assessor will evaluate outcome measures at three points: at baseline (T0), after the 16 therapy sessions weeks (T1), and 6 months after the end of treatment (T2). The primary outcomes were the scores from the Brief International Cognitive Assessment for Multiple Sclerosis (BICAMS). Data analysis will be performed to compare the efficacy of the two treatments. We expect superior efficiency of tablet-based SGT in contrast to conventional cognitive exercises, based on BICAMS measures of speed processing information and episodic memory.Ethics and dissemination The trial protocol is registered on ClinicalTrials.Gov (NCT04694534) and benefits from a favourable opinion from an ethics committee (RC-P0066-2018-A00411-54).